FINANCIAL POTENTIAL OF THE ENTERPRISE: STAGES OF MODELING AND DIAGNOSTIC+ - SHARAVARA, Roman; KONONENKO, Zhanna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Modelling diagnostics of the financial potential of the enterprise is an important tool for improving the efficiency of the enterprise's financial management and ensuring its stability and competitiveness in the market. This process helps identify the financial strengths and weaknesses of the business and develop strategies to overcome financial challenges and achieve success. Taking into account such features, the modelling of diagnostics of the financial potential of the enterprise can be explained as a process of analysis and assessment of the financial stability and capabilities of the enterprise based on various methods and models that allow forecasting and assessment of its financial profitability, liquidity, solvency and general financial condition. Modelling diagnostics of the financial potential of the enterprise is an important tool for making management decisions, ensuring the stability of the enterprise on the market and ensuring its development.The sequence of assessing the security and efficiency of using financial potential based on such a set of indicators can be presented as an algorithm that forms an idea of the stages of managing this process. The use of defined methods, methods and indicators of analysis to achieve the set specific goals of studying the diagnosis of the financial potential of the enterprise as a whole constitutes the methodology and methodology of its financial diagnosis.The classification of types of diagnosis of the financial potential of the enterprise is based on the peculiarities of conducting an analytical assessment of the activities of economic entities. It is based on the assessment of financial potential based on standard methods and models, such as balance sheet analysis, profit and loss statements, calculation of various ratios, application of methods of using modern financial instruments and technologies, such as financial models, artificial intelligence, big data analytics. The modelling mechanism for diagnosing the financial potential of the enterprise, focused on general management functions in the modern business environment, such as planning, control, decision-making and evaluation of results, becomes more effective and adaptive to the requirements and needs of the enterprise, subject to consistency and complementarity.
Keywords: modelling; enterprise diagnostics; financial potential; modelling tools; activity efficiency